Game addiction among adolescents and its’ health impacts - Sitti Nur Djannah; Fatwa Tentama; Rendi Ariyanto Sinanto (Intelektual Pustaka Media Utama, 2021)
Online gaming is a self-entertaining activity and can be addictive. Game addiction has a negative impact. This study aimed to determine the health belief model of adolescent game disorders on health impacts. This study used a qualitative phenomenology method. Data obtained through semi-structured interviews. The sample consisted of six participants. The results showed thatall participants felt vulnerable to disease, then overall realized the dangers of playing games such as staying up late, delaying eating, and delaying urinating. Then all participants learn about the benefits of reducing playtime and understand the importance of rest. Overall, all participants had the same obstacles, namely the invitation to make friends, boredom, free time, fun playing games, and not control themselves and the trend of electronic sports. Then an action stimulus was obtained, namely that all participants experienced changes in sleep patterns. All participants were sure and wanted to change their habits and continue to try, but it wasn't easy. Suggestions for participants to maintain health by limiting their playing hours to at least one hour a day to meet their physical needs.